General Banking Activities and Financial Performance Analysis: A case of Al Arafah Islamic Bank - Sabiha, Afsana (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.